2013
DOI: 10.1093/carcin/bgt304
|View full text |Cite
|
Sign up to set email alerts
|

SOCS2 mediates the cross talk between androgen and growth hormone signaling in prostate cancer

Abstract: Androgen induced SOCS2 ubiquitin ligase expression and inhibited GH signaling as well as cell proliferation and invasion in PCa, whereas reduced SOCS2 was present in castration-resistant cases. GH-signaling inhibitors might be a complementary therapeutic option for advanced PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Loss of SOCS2 and SOCS6 expression in hepatocellular carcinoma correlated with aggressive tumor progression and poor prognosis [85], and similar effects are seen in the case of SOCS2 and prostate cancer or breast cancer [77,86,87]. Methylation-mediated down-regulation of SOCS3 has been shown to be related to the abnormal cell growth and migration in same disease, which is mediated through loss of regulation of JAK/STAT and FAK signaling [88].…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 81%
See 1 more Smart Citation
“…Loss of SOCS2 and SOCS6 expression in hepatocellular carcinoma correlated with aggressive tumor progression and poor prognosis [85], and similar effects are seen in the case of SOCS2 and prostate cancer or breast cancer [77,86,87]. Methylation-mediated down-regulation of SOCS3 has been shown to be related to the abnormal cell growth and migration in same disease, which is mediated through loss of regulation of JAK/STAT and FAK signaling [88].…”
Section: Socs Proteins In Rtk Regulated Diseasesmentioning
confidence: 81%
“…Given the ability of SOCS proteins to modulate RTK signaling, transcriptional regulation of SOCS genes can provide a means of cross-talk between RTKs and other signaling pathways. It was recently demonstrated that SOCS2 expression is induced by androgens in prostate cancer cells which in turns down-regulates Src tyrosine kinase, a key mediator of RTK signaling [22]. Epigenetic silencing by DNA methylation is another layer of regulatory control of SOCS gene expression that may be of relevance for their biological actions.…”
Section: Socs Proteins In Rtk Regulationmentioning
confidence: 99%
“…The role of SOCS2 in cancer has been controversial (52)(53)(54)(55). In prostate cancer, it was reported that SOCS2 protein levels are reduced in CRPC and that SOCS2 inhibits the oncogenic events caused by growth hormone, such as cell proliferation and invasion (56). In contrast, another report revealed that SOCS2 protein expression was increased in prostate tumor tissues compared with benign tissues and that SOCS2 has a growth-promoting role in vitro and in vivo (57).…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of GHR-STAT5-SOCS2 signaling pathway is also associated with metabolic disorders [17,26,51,[80][81][82][83][84]. An inefficient GHR-JAK2-STAT5b signaling pathway results in fatty liver and adiposity in rodents and humans due to enhanced lipogenesis and reduced triglyceride secretion as well as reduced lipolysis [4,80,81].…”
Section: Other Functions Of Gh In the Regulation Of Body Weightmentioning
confidence: 99%
“…Thus, it has recently reported that in a sheep model, a point mutation in the SOCS2 gene not only resulted in higher body weight and size but also elevated leukocytes count in the milk as a sign of enhanced inflammatory response [90]. In addition, altered SOCS2 expression has also been associated with malignancies [84,[91][92][93]. Therefore, how to target SOCS2-regulated pathways without causing negative side effects that systemic and chronic reduction in SOCS2 protein might cause is still a challenge.…”
Section: Other Functions Of Gh In the Regulation Of Body Weightmentioning
confidence: 99%